2022
DOI: 10.1186/s13287-022-02799-y
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone enhances stem cell maintenance and promotes lineage-specific differentiation in human embryonic stem cells

Abstract: Background Thyroid hormone triiodothyronine (T3) is essential for embryogenesis and is commonly used during in vitro fertilization to ensure successful implantation. However, the regulatory mechanisms of T3 during early embryogenesis are largely unknown. Method To study the impact of T3 on hPSCs, cell survival and growth were evaluated by measurement of cell growth curve, cloning efficiency, survival after passaging, cell apoptosis, and cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Other studies prove that the influence of thyroid hormones on VEGF expression is related not so much to the function of the hormones as to the amount of endocrine-active tissue. 39,40 In our study, we observed that the expression of VEGFA and VEGFC genes in the MSC of the umbilical cord collected from hypertensive women is statistically significantly higher compared to healthy women. A team of researchers from India assessed the expression of VEGF in umbilical cord tissues depending on the severity of hypertension.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Other studies prove that the influence of thyroid hormones on VEGF expression is related not so much to the function of the hormones as to the amount of endocrine-active tissue. 39,40 In our study, we observed that the expression of VEGFA and VEGFC genes in the MSC of the umbilical cord collected from hypertensive women is statistically significantly higher compared to healthy women. A team of researchers from India assessed the expression of VEGF in umbilical cord tissues depending on the severity of hypertension.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies prove that the influence of thyroid hormones on VEGF expression is related not so much to the function of the hormones as to the amount of endocrine-active tissue. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Common upregulated DEGs included TP63 and TGM6 54 , which were involved in response to environmental in ammation and ER stress. DIO2, which converts thyroxine (T4) to triiodothyronine (T3), is crucial for stem cell maintenance and TE lineage differentiation 55 . The common downregulated DEGs included DDIT4 and DUT, which are involved in key recovery mechanisms in response to cell damage.…”
Section: Differential Expression (De) Analyses Revealed Distinct Patt...mentioning
confidence: 99%
“…CellChat package (version 1.1.0) 55 was used to infer the global cell-cell communication in euploid and aneuploid cells of the 3 mosaic embryos, based on ligand-receptor interactions. We followed default parameters except for the application of projectData function, which projects gene expression data onto protein-protein interaction (PPI) networks.…”
Section: Ligand-receptor Interactome Analysismentioning
confidence: 99%
“…The human thyroid gland, which is located at the base of the neck and wraps around the trachea just below the cricoid cartilage (1,2), is a very important endocrine organ, responsible for secreting thyroid hormones to maintain normal functioning of the body. Thyroxine (T4) and triiodothyronine (T3) play extremely important roles in protein synthesis, temperature regulation, and energy generation and regulation (3)(4)(5). Part of the T3 and T4 synthesized by and secreted from the thyroid gland combines with protein in the blood and is preserved temporarily, and the rest circulates as free forms known as FT3 and FT4, which are ready at any time to play their roles (6,7).…”
Section: Introductionmentioning
confidence: 99%